Glaukoma yang Diinduksi Steroid Oculi Dextra Et Sinistra - Rahmanindya Defiyandini Puteri; M. Yusran (Medula, 2020)
Steroids are a group of anti-inflammatory drugs, commonly used to treat ocular and systemic conditions. Unmonitored use of steroids especially in eye drop formulations is common in situations when it is easily available over-the-counter, resulting in undesirable side effects. Ms. L, 17 years old, both eyes could not see without red eyes since 8 months ago. Initially the patient feels increasingly blurry until finally unable to see. Before experiencing this the patient had a history of using eye drops cointaing steroid for almost 1 year because her eyes were often red. Ophthalmological examination obtained vision oculus dextra: ½/60, vision oculus sinistra 1/300, no injection of right and left conjunctiva, deep right and left front chambers, pupillary light reflexes decreased in both eyes, right and left clear lens, oculi tension N+1 per palpation, narrow vision field, and in fundoscopic examination found cupping of the optic disc with cup disc ratio of 0.9, nasalisation of blood vessels and lamina cribosa were clearly seen in both eyes. Therapy given to this patient was Timolol maleate 0,5% eye drop 1 drop /12 hours and Latanoprost 0.005% eye drop 1 drop /24 hours. Patients were also planned for trabeculectomy surgery.